2016
DOI: 10.3389/fnhum.2016.00348
|View full text |Cite
|
Sign up to set email alerts
|

Shutting Down Sensorimotor Interferences after Stroke: A Proof-of-Principle SMR Neurofeedback Study

Abstract: Introduction: Neurofeedback training aims at learning self-regulation of brain activity underlying cognitive, emotional or physiological functions. Despite of promising investigations on neurofeedback as a tool for cognitive rehabilitation in neurological diseases, such as after stroke, there is still a lack of research on feasibility and efficiency of neurofeedback in this field.Methods: The present study aimed at investigating behavioral and electrophysiological effects of 10 sessions of sensorimotor rhythm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 59 publications
0
29
3
Order By: Relevance
“…This postulation is also confirmed by studies aiming at modulating brain activity and connectivity in stroke with fNIRS ( Mihara et al., 2012 , Mihara et al., 2013 ), MEG ( Boe et al., 2014 , Buch et al., 2012 ), or EEG ( Ramos-Murguialday et al., 2014 , Shindo et al., 2011 , Young et al., 2014 ). Notably, evidence exists for a successful use of EEG neurofeedback for cognitive and motor rehabilitation in stroke, but the effects are not consistent across participants ( Bearden et al., 2003 , Cannon et al., 2010 , Doppelmayr et al., 2007 , Reichert et al., 2016 , Rozelle and Budzynski, 1995 ). We posit that, thanks to its superior spatial resolution, rt-fMRI can provide more accurate feedback than EEG/MEG and fNIRS to the participants, who may more easily learn to control their brain activity or connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…This postulation is also confirmed by studies aiming at modulating brain activity and connectivity in stroke with fNIRS ( Mihara et al., 2012 , Mihara et al., 2013 ), MEG ( Boe et al., 2014 , Buch et al., 2012 ), or EEG ( Ramos-Murguialday et al., 2014 , Shindo et al., 2011 , Young et al., 2014 ). Notably, evidence exists for a successful use of EEG neurofeedback for cognitive and motor rehabilitation in stroke, but the effects are not consistent across participants ( Bearden et al., 2003 , Cannon et al., 2010 , Doppelmayr et al., 2007 , Reichert et al., 2016 , Rozelle and Budzynski, 1995 ). We posit that, thanks to its superior spatial resolution, rt-fMRI can provide more accurate feedback than EEG/MEG and fNIRS to the participants, who may more easily learn to control their brain activity or connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that SMR NF training might facilitate thalamic inhibitory mechanisms and block motor activity that interferes with information processing (Sterman, 1996). SMR NF training improved declarative memory (Hoedlmoser et al, 2008;Gruzelier, 2014;Schabus et al, 2014;Kober et al, 2015;Cho et al, 2016;Reichert et al, 2016) and attention (Vernon et al, 2003;Egner and Gruzelier, 2004;Lecomte and Juhel, 2011;Kober et al, 2015) in elderly patients. Theta rhythm (4-7 Hz) is associated with neurological and psychological functions in the limbic system.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the amplitude of N200 and P300 indicates the normalization of neural circuits associated with discrimination of stimuli and updating of attention 17 . In a study by Reichert et al (2016), an increase in N100 and P300 amplitude was observed in a post-stroke patient in an experimental group who had SMR training, whereas the control group showed no difference 18 . This finding is in line with our study that found no differences in N100 and P300 amplitude in healthy participants after SMR NFB training.…”
Section: Discussionmentioning
confidence: 96%